HAHNEMAN’S PRINCIPLES AND ANTHROPOLOGY OF TRANSCENDENT PHILOSOPHY: Some Observations in the Light of Islamic Sources - Hanafi Mohd. Nor (Sekolah Tinggi Agama Islam Sadra, 2011)
This paper seeks to retrace human nature and transcending the vision of humanity, by identifying, describing and analyzing the Hahnemannian principles and their relevance to anthropology of transcendent philosophy. Using the qualitative data from Hahnemann’s works with special reference to his Organon we found that Hahnemann’s principles are, unquestionably, a philosophical system in its own right. The primary goal of his philosophy, however is not solely speculative, indeed it is a medical philosophy written in brief aphoristic style, aimed more of guidelines at curing suffering human beings, rather than winning adherents to its speculative creed. The main concern of Hahnemann with regard to his medical philosophy is actually the question of suffering human well-being. The answer to this question will provide an indication of the relevant of Hahnemannian principles to anthropology of transcendent philosophy. Thus Hahnemann’s principles cannot be properly understood apart from some grasp of his conception of human nature and philosophy as a whole. Nonetheless his ideas are against the new emergence mainstream thought pattern of modern Europe which in turn spread all over the globe.